Quality of Life and Its Relevant Factors in Menopausal Women - Mahboobehn Kafaei-Atria; Saeide Nasiri; Fateme sadat Izadi-Avanji; Fatemeh Abbaszadeh (Guilan University of Medical Sciences, 2022)
Abstract: Introduction: Menopause is an essential part of human life that affects women's quality of life (QOL). Objective: This study investigated the quality of life and some relevant factors in menopausal women. Materials and Methods: This cross-sectional study was conducted on 45-60 years old menopausal women in 3 areas of Kashan city, Iran in 2018. By cluster sampling method, 236 participants were included in the study. The study questionnaires consist of demographic and obstetric information and menopausal quality of life (MENQOL). The Kolmogorov-Smirnov test, t test, the Pearson and Spearman correlation tests, as well as linear regression analysis, were used for data analysis. Results: The mean ±SD age of the women was 52.65 ±3.67 years. Also, their mean±SD years lapsed menopause was 2.89 ±1.53, and the mean ±SD for QOL was 31.24 ±11.47. There were no significant correlations between QOL and women's age, menopausal age, and elapsed years since menopause. Based on linear regression analysis, the variables of age (B= 2.61, 95%CI; 0.46-4.77, P=0.02), menopausal age (B= -2.19, 95%CI; -4.39 - -0.01, P=0.049), and satisfaction of spouse ((B= -4.90, 95%CI; -8.45- -0.35, P=0.007) remained in the model as relegated variables to quality of life (R2 = 11.8%). Conclusion: Since most women had moderate menopausal QOL score, intervention programs to improve the QOL for postmenopausal women is recommended in health centers. Further studies are suggested to evaluate the quality of life in chronic diseases of postmenopausal women.